(untitled) (EU and comparative law issues and challenges series (ECLIC), 2020)
A successful manager knows how to successfully lead a team, and the more satisfied the employees are, the more they are willing to contribute. The final result is a better company image in the market and positive economic performance indicators. Company profits when the organization continually invests in developing the business capabilities of managers to manage their teams. This paper contains managerial specific challenges, outlines the profile of an emotionally intelligent leader, and compares leadership styles in the context of EU, on the example of animation in Croatian tourism. The aim of the paper is to show how emotional intelligence influences the capabilities of animation team managers in business tasks. It will be pointed out how a manager can improve his or her emotional and communication skills. The animation manager develops emotional intelligence and communication skills by integrating technology into the business of his animation team. The descriptive method and method of compilation are used to define emotional intelligence in european practice. Questionnaire is made for analysis, to detect how significant is correlation between development of emotional intelligence and usage of information-communication technology in an animation.